Vulnerability assessment of an innovative precast concrete sandwich panel subjected to the ISO 834 fire. (15th July 2022) - Kontoleon, K.J.; Georgiadis-Filikas, K.; Tsikaloudaki, K.G.; Theodosiou, T.G.; Giarma, C.S.; Papanicolaou, C.G.; Triantafillou, T.C.; Asimakopoulou, E.K.
Abstract: Development and use of preconstruction have been exhibited for several decades. Numerous modules, ranging from the simplest to the most advanced concepts, have been suggested to ameliorate the layout of building structures, with respect to a broad spectrum of needs. This study aims to unfold the fire defensiveness of an innovative precast concrete sandwich wall-system subjected to the ISO 834 fire, such as this is provided for in EN1991-1-2. In light of a rapidly evolving environment that should shield structures against fire, this investigation emphasises on the vulnerability of precast panels with a varying thickness of insulation by means of a numerical methodology and a versatile heat transfer-model. A finite-element analysis is carried out with COMSOL Multiphysics® simulation software. In a following step, as fire risk should be vigorously tackled, the research is extended to validate numerical predictions of the model by means of an experimental setup for wall specimens arranged in the laboratory. Therefore, an additional goal of this research is to assess temperature discrepancies for both addressed cases. Despite various approximations of the model, an excellent agreement between numerical and experimental results is shown, confirming the rationality of computational simulations in terms of temperatures' precision. It has been revealed that for all examined cases, the insulation ability (I) has been maintained for more than 3 h regardless of the positioning of the insulation. Further evidence though suggested that is not the case for the loadbearing capacity (R), as the installation of a fire exposed insulation layer resulted in lower stability systems. Also, the effect of the insulation thickness is not that dominant as on average and maximum temperature deviations among marginal assemblies ( d EPS  = 2 cm and d EPS  = 10 cm) did not exceed 5 °C and 10 °C at t fire  ≈ 100 min. Graphical abstract: Image 1 H ighlights: Thermal analysis of precast concrete sandwich wall system exposed to a fire attack. Adoption of temperature-dependent material properties under elevated temperatures. Modelling technique for numerical treatment of EPS decomposition and render fall. FEA-based simulations with respect to the thickness and position of EPS insulation. Validation of the model and degree of agreement by means of a medium-scale test.